A systematic review of the technology-based assessment of visual perception and exploration behaviour in association football - McGuckian, T. B.; Cole, M. H.; Pepping, G.-J. (Journal of Sports Sciences, 2018)
To visually perceive opportunities for action, athletes rely on the movements of their eyes, head and body to explore their surrounding environment. To date, the specific types of technology and their efficacy for assessing the exploration behaviours of association footballers have not been systematically reviewed. This review aimed to synthesise the visual perception and exploration behaviours of footballers according to the task constraints, action requirements of the experimental task, and level of expertise of the athlete, in the context of the technology used to quantify the visual perception and exploration behaviours of footballers. A systematic search for papers that included keywords related to football, technology, and visual perception was conducted. All 38 included articles utilised eye-movement registration technology to quantify visual perception and exploration behaviour. The experimental domain appears to influence the visual perception behaviour of footballers, however no studies investigated exploration behaviours of footballers in open-play situations. Studies rarely utilised representative stimulus presentation or action requirements. To fully understand the visual perception requirements of athletes, it is recommended that future research seek to validate alternate technologies that are capable of investigating the eye, head and body movements associated with the exploration behaviours of footballers during representative open-play situations.